The Role of Health and Medical Professions in Indonesia - Sutomo, Adi Heru (International Journal of Medical and Health Sciences Research, 2015)
Introduction: In the context of public health, there are many problems in Indonesia, for instances the variation of many islands like Java , Sumatra, Kalimantan, Papua, Bali, Nusa Tenggara and so on, the huge number of population, the variation of tribes, income, public health services, the making of public health policy and so on. In relation to the above mentioned, then the application of public health program are need to be taken into mind, because of based on that there will be the variations of role of health and medical profession in the many differences of occupations. Method & Discussion: this paper is made based on library studies that compile from many data which hopefully can be used to construct the right of scientific writing in the context of public health sciences in relation to the General Medicine. Result & Discussion: quite clear that there are many public health aspects that need to be taken into policy in relation to clinical aspects, health financing aspects, health economic aspects, and the like which in general it will come to at least the understanding of primary health services and secondary health services functions. There is a need to develop the real and perfect program of the General Physician who can be used to support the Primary Health Centre. It means that what the Indonesian need to be implemented is not only the health financing program, but also the right Medical Education Program, the right Family Medicine Program, the right Primary Health Care, the right Population Health Care, and so on. Conclusion: there is a need to manage the role of health and medical profession in Indonesia in a specific way, where then based on that they can work together in a harmony with many other occupations, for instance sociologist, psychologist, lawyer, technique experts, and so on.